The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1en00853f
|View full text |Cite
|
Sign up to set email alerts
|

In situ decoration of La(OH)3 on polyethyleneimine-linked dendritic mesoporous silica nanospheres targeting at efficient and simultaneous removal of phosphate and Congo red

Abstract: La(OH)3 and polyethyleneimine functionalized 3D dendritic mesoporous silica spheres as novel porous adsorbents efficiently removed phosphate and Congo red. In P/CR binary solution, the formed LaPO4 promoted the simultaneous adsorptive removal of CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Take 6-mercaptopurine as an example: apart from the characteristic absorption peaks of La­(OH) 3 , additional peaks of 6-mercaptopurine assigned to V C–S and V purine could be identified, and the La–O bond disappeared apparently (Figure S9). The destruction of the intrinsic La–O bond indicated that the coordination interaction formed as 6-mercaptopurine adsorbed onto La­(OH) 3 , probably interacting with the N of the purine ring or sulfydryl . After Au@AgNPs were decorated onto La­(OH) 3 , the shift of the N 1s peak suggested that there was a coordination interaction between the purine ring and La­(OH) 3 –Au@AgNPs, and the XPS peak of S 2p at 162.2 eV was originated from the metallic sulfur bond (Figure S10).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Take 6-mercaptopurine as an example: apart from the characteristic absorption peaks of La­(OH) 3 , additional peaks of 6-mercaptopurine assigned to V C–S and V purine could be identified, and the La–O bond disappeared apparently (Figure S9). The destruction of the intrinsic La–O bond indicated that the coordination interaction formed as 6-mercaptopurine adsorbed onto La­(OH) 3 , probably interacting with the N of the purine ring or sulfydryl . After Au@AgNPs were decorated onto La­(OH) 3 , the shift of the N 1s peak suggested that there was a coordination interaction between the purine ring and La­(OH) 3 –Au@AgNPs, and the XPS peak of S 2p at 162.2 eV was originated from the metallic sulfur bond (Figure S10).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The destruction of the intrinsic La−O bond indicated that the coordination interaction formed as 6mercaptopurine adsorbed onto La(OH) 3 , probably interacting with the N of the purine ring or sulfydryl. 43 After Au@AgNPs were decorated onto La(OH) 3 , the shift of the N 1s peak suggested that there was a coordination interaction between the purine ring and La(OH) 3 −Au@AgNPs, and the XPS peak of S 2p at 162.2 eV was originated from the metallic sulfur bond (Figure S10). 44 In conclusion, the rapid enrichment was mainly attributed to physical adsorption, coordination interaction, and the metallic sulfur bond.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4c, two sets of bimodal peaks ascribed to La 3d 3/2 and La 3d 5/2 of BOL-2 can be fitted into four peaks at binding energies of 851.83/855.44 eV and 834.80/838.79 eV, respectively, suggesting the presence of La 3+ in the form of La(OH) 3 . 11,38 Compared with La 3d of pure La(OH) 3 shown in Fig. 4d, all these four peaks in BOL-2 are observed to shift to higher binding energies, indicating the formation of La(OH) 3 /(BiO) 2 -OHCl heterojunctions in BOL-2.…”
Section: Surface Compositionmentioning
confidence: 91%
“…The influence of the pH was evaluated from pH 2 to 10 ( Gao et al, 2021;Huang et al, 2021a;Khan and AL-Thabaiti, 2022). 50 mL of 50 ppm dye solutions were prepared.…”
Section: Ph Influencementioning
confidence: 99%
“…At pH 4, the adsorption capacity is a little lower than at higher pH, probably due to the electrostatic repulsion effect between positively charged adsorbate and the acidic form of CR, which has positive charges on its amine groups (-NH3 + ) (Aoopngan et al, 2019;Zheng et al, 2021). At pH higher than 5.0, CR molecules get a negative charge due to deprotonation of the -SO3H groups, generating -SO3groups (Huang et al, 2021b). Those groups are expected to have an electrostatic attraction with the LAB surface, which is positively charged in this range of pH.…”
Section: Ph Influencementioning
confidence: 99%